Review of Postcolonial Poetics by Elleke Boehmer - Nyikos, Daniel (AMERICANA E-journal of American Studies in Hungary, 2018)
Postcolonial Poetics. 21st-century Citical Readings Elleke Boehmer Oxford: Palgrave Macmillan, 2018 220 pages ISBN: 978-3319903408